Suction and strength of unsaturated soils - Bulolo, Sam (Nanyang Technological University, 2021)
This study focused on two major aspects of unsaturated soils: suction and strength measurements with an emphasis on methods that are more accessible to practitioners. Tests were performed on reconstituted clay and compacted residual soil. The filter paper method is still very useful for suction measurement and this study proposes to use electrical resistivity in place of the water content of the filter paper to infer suction to overcome some of the limitations of determining the latter. The current osmotic technique of controlling matric suction was improved using reverse osmosis membrane and sodium chloride solutions. New shear strength equation incorporating suction stress that took into account the availability of data for constant suction and constant water content direct shear tests was proposed. Lastly, Brazilian tensile strength tests were conducted, and a new tensile strength model was developed for both coarse and fine-grained soils.